2018
DOI: 10.1111/jai.13805
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationships for 19 Scorpion fishes (Scorpaenidae) from Visakhapatnam coast, India

Abstract: This study presents the length–weight relationships (LWRs) for 19 scorpionid species from Visakhapatnam coast, India. Samples were collected fortnightly between December 2010 and December 2013 from commercially operated fishing gears viz. gill nets (Hung length: 115–143 m and mesh size: 100–270 mm) operated at 20–30 m depth, shore seines (mesh size: 10–20 mm), trawls (head rope length: 37–46 m and cod end mesh size: 15–32 mm) operated at depth of 20–50 m from a fishing vessel of 9.6–11.1 m length overall (LAO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…For the selected fish species, calculated “ b ” values were within the estimated range of 2.5 to 3.5 (Froese, ). Most of the length‐weight relationships reported in this study agreed with those obtained previously by Govinda Rao, Krishna, & Sujatha, ; Govinda Rao et al, (); Sujatha, Shrikanya, and Krishna () and Naranji, Velamala, and Kandula () in the Visakhapatnam coastal waters. Present research work has been limitation as the specimens were together from deep sea trawl nets only which are highly influenced and selective in environment.…”
Section: Discussionsupporting
confidence: 92%
“…For the selected fish species, calculated “ b ” values were within the estimated range of 2.5 to 3.5 (Froese, ). Most of the length‐weight relationships reported in this study agreed with those obtained previously by Govinda Rao, Krishna, & Sujatha, ; Govinda Rao et al, (); Sujatha, Shrikanya, and Krishna () and Naranji, Velamala, and Kandula () in the Visakhapatnam coastal waters. Present research work has been limitation as the specimens were together from deep sea trawl nets only which are highly influenced and selective in environment.…”
Section: Discussionsupporting
confidence: 92%
“…In marine fishes, ovoviviparity is well-known to occur in ~ 55% (515 species) of chondrichthyan fishes, but only ~ 2-3% (510 species) of bony (Wourms and Demski 1993;Yamada and Kusakari 1991). Naranji et al (2018) reported length-weight relationship of 19 scorpaenid fish species from the Indian coast. Sawcheek scorpionfish, B. serrulata, has been considered a well-conserved fish species (Grandcourt et al 2004) with a broad distribution on both sides of the Indo-Pacific and in some areas of Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 99%
“…They have moderately compressed and slightly robust bodies with spiny heads and venom glands at the base of needle‐like dorsal fin spines through which they can inject the deadliest of fish neurotoxins (Nelson et al, 2016). Most of the small, bottom‐dwelling stonefishes are found throughout the tropical marine waters of the Pacific and Indian Oceans, from Japan to Australia west to the western Indian Ocean and Red Sea, being usually found near the seashore in shallow waters, but also reaching depths of up to 420 m (Eschmeyer et al, 1979; Amaoka & Kanayama 1981; Mandrytsa 1990, 1993; Nelson et al, 2016; Naranji et al, 2018; Fricke et al, 2021). Stonefishes are mostly found associated to coral reefs, where they live benthically and camouflage as rocks over muddy or sandy substrates, using their pectoral fins for burying and “walking” on the bottom (Nelson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%